تقويم الاداء وتقدير بعض المعالم الوراثية لصفات كمية في محصول الشعير Hordeum spp - Jasim M. Aziz; Yaser H. Homadia; Raid M. Abdullah (Kirkuk Journal of Science, 2017)
seven varieties of Barley was carried out wtich were (Brag , Shahah , Al-KHeer , Al-Wrkai , Sameer ,Al-Hadher and Amal ) have been grown in seasonal 2014 -2015 and 2015 -2016 in the province of Kirkuk, using Randomized Complete Block Design with three replicates, included the characteristics of number of days for the expulsion of spikes 50% of plants ,plant height (cm) ,spike length (cm) , number of spikes / m2 , number of grains spike , weight of a thousand grian(g) and grain yield (kg / ha) , notes that the product was Sameer may outweigh the number of spikes / m2 on average for seasonal (355.5 spike / m2) and yield grain (kg / ha) in the first season was (3463 kg / ha), but obtained fell in the second season and gave less obtained was (3022.3 kg / ha) , superiority Al-Kheer variety at a rate of (3600 kg / ha) , Amal variety was surpassed in the number of grain Spike and Shuaah in the weight of a thousand grains .This variation in the traits between varieties gives an indication of the possibility incorporated in education programs by hybridization in order to collect desired characteristics in the synthesis of certain hereditary, also notes that the genetic and phenotypic differences were a burden and moral in all attributes except the weight of a thousand grain an indication that the HLA dominant in inheriting and is reflected in the values of heritability in the broad sense as she was high except spike length in the first season, correlations and regression noted that the number of spikes and the number of grains spike and the weight of a thousand grain the most important qualities that have an impact on changes holds that occur on the grain barley crop and can be adopted as indicators of electoral improved .